Child by Child: The Comer Process for Change in Education - Comer, James P.; Ben-Avie, Michael; Haynes, Norris M.; Joyner, Edward (Teachers College Press, 1999)
Keywords: Comer, James P; School improvement programs; Parent participation; United States; United States; Child development; United States; Community and school; United States; Education; United States; Educational change; United States; Student participation in administration; dept.csp; faculty_collection

Rallying the Whole Village: The Comer Process for Reforming Education - Comer, James P.; Ben-Avie, Michael (Teachers College Press, 1996)
Keywords: Comer, James P; Educational change; Training of; United States; United States; Child development; United States; Community and school; United States; Education, Urban; United States; Educational evaluation; United States; School environment; United States; School improvement programs; United States; Teachers; dept.csp; faculty_collection

Counseling for College: A Professional's Guide to Motivating, Advising, and Preparing Students for Higher Education - Matthay, Eileen R. (Peterson's, 1995)
Keywords: Admission; Counseling in secondary education; United States; United States; Universities and colleges; dept.csp; faculty_collection

Counseling for College: A Professional's Guide to Motivating, Advising, and Preparing Students for Higher Education - Matthay, Eileen R. (Peterson's Guides, 1991)
Keywords: Admission; Counseling in secondary education; United States; United States; Universities and colleges; dept.csp; faculty_collection

Comparison of scores of bilingual urban and monolingual suburban elementary school children for two measures of intelligence - Murphy, D.G. (Psychological Reports, 1990)
Keywords: article; child; dept.csp; human; intelligence; language; mental test; normal human

Preliminary study of effect of decision making on locus of control among prison inmates - Murphy, D.G. (Psychological Reports, 1990)
To study the effect of teaching decision-making to inmates in a maximum security facility on locus of control 19 adult male inmates who were incarcerated at a community correctional center were pre- and posttested on the Rotter Internal-External Locus of Control Scale. In this preliminary study there was no statistically significant difference at pretest or posttest so teaching decision-making skills in group settings versus teaching in a group combined and one-to-one contact did not affect locus of control as measured. This personality trait appears stable over time and a more thorough means of intervention is required to effect change.
Keywords: adult; article; clinical article; decision making; dept.csp; human; male; personality; prisoner

Gifted: the end of a tail. - Falk, Carolyn R (Gifted Education International, 1990)
Special education in the United States services a diverse population, including those students whose academic performance falls at the ends of the normal distribution. This article challenges the assumption that a continuum of learning opportunities appropriate for exceptional persons is possible when the concept of the normal distribution is used. An alternate model, a bull's-eye, is suggested to accommodate the openended potential for the gifted population. © 1990 A B Academic Publishers Printed in Great Britain.
Keywords: dept.csp

Promoting holistic child development: a collaborative school health approach. - Haynes, N.M. (The Journal of school health, 1998)
Keywords: *Child Development; *Health Promotion/og [Organization & Administration]; *Holistic Health; *School Health Services/og [Organization & Administration]; Adolescent; Child; Child Development; Cooperative Behavior; Faculty; Health Promotion; Health Services Needs and Demand; Holistic Health; Humans; School Health Services; Social Support; United States; adolescent; child; child development; cooperation; dept.csp; health promotion; health service; human; organization and management; philosophy; review; school health service; social support; university

School factors in substance abuse prevention among young male African Americans - Haynes, NM; Troutman, MR; Nwachuku, U (Journal of Educational and Psychological Consultation, 1998)
Despite reports that substance abuse among young Americans is on the decline, the problem among young male African Americans continues to be of major concern. School-based prevention strategies offer promising alternatives for reducing the risk factors for substance abuse among this group. The most successful of these programs appear to be those that include the entire school ecology as part of the prevention strategy and focus on the unique psychosocial development needs of these youth. in this article we discuss the prevalence of substance abuse among male African American youth, examine school correlates and risk factors, and review school-based prevention strategies that have shown varying degrees of effectiveness in addressing the substance abuse problems, directly through changing values, attitudes, and behaviors, and indirectly by reducing risk factors and strengthening protective mechanisms.
Keywords: dept.csp